Strengthening Teacher Development in Pesantren: The Role of Human Resource Management Practices in Ta’hilu al-Mudarrisin - Hazaa, Zuhair Mubarrak; Aziz, Abdul; Abidin, Zainal; Tumangger, Maruli; Gunawan, Indra (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyse the principles and practices of human resource management (HRM) in the Ta’hilu al-Mudarrisin (teacher development) program in Islamic schools and evaluate its impact on improving pedagogical competence, ethical standards, and adaptability to changes in educational regulations. This study used a descriptive qualitative methodology with case study techniques in several Islamic boarding schools (pesantren). Data were collected through observation, in-depth interviews with principals, program administrators, teachers, and students, and analysis of training documents and supervision reports. The results indicate that strict supervision and reflective methods effectively improve teaching quality, pedagogical competence, and student achievement. The program also plays a role in enhancing educational ethical standards and responsiveness to regulatory changes. However, program implementation faces obstacles such as limited resources and time, which can be overcome through task reorganisation and capacity building. The implications of this study underscore the importance of integrating strict supervision, capacity-building, and spiritual enrichment to foster a progressive educational environment in Islamic schools.